Victorian Studies’ International Publics: The California Dickens and Global Circulation Projects - Gagnier, Regenia (Romanticism and Victorianism on the Net, 2009)
AbstractAt a time when British funders of Higher Education are calling for more social and economic impact of humanities research and U.S. funders for innovation, the California Dickens Project and the Global Circulation Project are exemplary of humanities with a public face. The Dickens Project has recently begun to redeploy the defunct archive of International Dickens, and the British Academy-funded Global Circulation Project has begun a map and dialogue on the circulation of literatures in contact. They revive cross-cultural dialogue on deep notions of freedom and choice that have been obscured for a half-century.